2000
DOI: 10.1002/etc.5620191114
|View full text |Cite
|
Sign up to set email alerts
|

Dietary absorption efficiencies and toxicokinetics of polychlorinated biphenyls in ring doves following exposure to aroclor® mixtures

Abstract: Ring doves (Streptotpelia risoria) were fed a meal of pellets spiked with an Aroclor® mixture. Feces were collected from birds after fasting 31 h postexposure and dietary absorption efficiencies (AbE) of polychlorinated biphenyls (PCBs) were determined by mass balance. Polychlorinated biphenyl AbEs ranged from 0.86 to 0.97 for individual congeners and were similar to the lipid AbE of 0.90. The AbEs exhibited a declining trend with increasing chemical hydrophobicity. The toxicokinetics of PCBs and dietary lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 39 publications
4
65
2
Order By: Relevance
“…The term G represents the volume of contaminated oil (l/d) gavaged to the bird on a given day; AE is the chemical assimilation efficiency from ingested oil; k b is the congener-specific, wholebody elimination rate constant (1/d); and k g is the growth dilution rate constant (1/d). Initial simulations assumed AE to equal 0.95, because previous studies have established that dietary absorption efficiencies of PCBs in birds range from 0.9 to 0.97 [8]. The whole-body elimination rate constant (k b ) was estimated from PCB plasma clearance rate constants ( ; ml plasma/g BW/d) kЈ pc measured for adult male American kestrels [7].…”
Section: Bioaccumulation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The term G represents the volume of contaminated oil (l/d) gavaged to the bird on a given day; AE is the chemical assimilation efficiency from ingested oil; k b is the congener-specific, wholebody elimination rate constant (1/d); and k g is the growth dilution rate constant (1/d). Initial simulations assumed AE to equal 0.95, because previous studies have established that dietary absorption efficiencies of PCBs in birds range from 0.9 to 0.97 [8]. The whole-body elimination rate constant (k b ) was estimated from PCB plasma clearance rate constants ( ; ml plasma/g BW/d) kЈ pc measured for adult male American kestrels [7].…”
Section: Bioaccumulation Modelmentioning
confidence: 99%
“…Simulations also were performed using congener-specific PCB AEs as measured in ring doves [8]. Addition of congenerspecific AEs did not improve the model fit based on goodnessof-fit tests (data not shown).…”
Section: Bioaccumulation and Retention Of Pcbsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was observed that many OCs increased in concentration with each trophic level in aquatic food webs, a process termed biomagnification. Uptake rates of most hydrophobic OCs are similar between species (see, e.g., [4]), and the elimination rate is what determines whether a chemical biomagnifies. Chemicals with fast elimination are less likely to biomagnify.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have documented that birds can accumulate PCBs through their diet (Custer et al 1998(Custer et al , 1999(Custer et al , 2003(Custer et al , 2005Drouillard and Norstrom 2001;Froese et al 1998;Secord et al 1999). Effects of PCBs on birds, and especially on chickens (Gallus domesticus), which are extremely sensitive, have been clearly demonstrated in laboratory studies (Hoffman et al 1996b).…”
Section: Introductionmentioning
confidence: 99%